Bilateral rubber hand illusion induced by unilateral visuotactile stimulation - Yamamoto, Shinya (i-Perception (London), 2024)
The rubber hand illusion involves the sense of body ownership of a fake hand. We showed that concurrent visuotactile stimuli to unilateral rubber and real hands can induce the embodiment of bilateral rubber hands when both rubber hands are positioned on the table. This phenomenon indicates that the brain has an integrated representation of the sense of body ownership for both hands.